Reaching the 'New Normal': A Wish for Breast Cancer Patients in Palliative Care - Kristiani Sitorus; Enie Novieastari; Tuti Nuraini (JURNAL INFO KESEHATAN, 2025)
More than 80% of breast cancer patients in Indonesia who are diagnosed are at an advanced stage. Advanced cancer treatment is directed at palliative care from the beginning of diagnosis.  Patients undergoing palliative care must adjust to the changing needs that occur during palliative care in line with the decline in the condition of the disease and the impact of its treatment. It can affect changes in the patient's daily life patterns. This study was conducted to explore the unmet needs of breast cancer patients during palliative care in the context of the culture and healthcare system in Indonesia. This study utilized a descriptive qualitative phenomenological method. In-depth interviews with semi-structured interview guidelines were conducted on 14 breast cancer patients undergoing palliative care. The thematic analysis uses the Colaizzi approach. The results of this study obtained three specific themes of unmet needs in the study participants: 1) the need to achieve the 'New Normal' to return to activities with enthusiasm and hope, 2) the need for appreciation and recognition, and 3) Support to overcome the fear of death and the uncertainty of the future. Breast cancer patients want to return to their activities with enthusiasm and hope despite facing physical limitations and emotional challenges. In conclusion, achieving the 'New Normal' is an important aspect of this adjustment process, which involves physical, emotional, social, and spiritual support. This finding differs from previous research, where other publications did not explicitly mention the need to achieve the 'New Normal'. Therefore, the role of nurses in addressing unmet needs, both in the context of the 'New Normal' and more generally, is crucial in palliative care for breast cancer patients. This support enhances the patient's quality of life and gives greater meaning to the remainder of their lives.